The Relationship of Personality Type with the Incident of Coronary Heart Disease in the Cvcu Room of Labuang Baji Rsud Makassar - Mahmud, Yantimala (Jurnal Perilaku Kesehatan Terpadu, 2022)
One of the heart diseases that causes the highest number of deaths in the world is coronary heart disease (CHD). In Indonesia, the prevalence of coronary heart disease based on a doctor's diagnosis is 0.5% or around 883,447 people, while based on a doctor's diagnosis and symptoms it is 1.5% or around 2,650,340 people. In South Sulawesi Province in 2014 there were 204 old cases of coronary heart disease and 104 new cases. In the city of Makassar in 2014, heart disease was still in second place with a total of 449 cases. In 2016, 253 people were diagnosed at Labuang Baji Makassar Hospital, 50 of whom were diagnosed with coronary heart disease. The aim of the research was to determine the relationship between personality type and the incidence of coronary heart disease in the CVCU Room at Labuang Baji Hospital, Makassar. The type of research is non-experimental research, analytical method, cross sectional design. The research was carried out in the CVCU Room at Labuang Baji District Hospital, Makassar, from 11 to 25 April 2017 with a sample size of 35 respondents using accidental sampling technique. The results of Fisher's exact test obtained a p value = 0.001 < 0.05, meaning that there is a relationship between personality type and the incidence of coronary heart disease in patients being treated in the CVCU Room at Labuang Baji Hospital, Makassar. It was concluded that type A personality is at greater risk of suffering from coronary heart disease compared to people who have type B personality. It is recommended that health service workers, especially nurses in the CVCU Room at Labuang Baji Hospital, Makassar, carry out psychological assessments to identify the type of personality the patient has.